Subacute Thyroiditis is Associated with HLA-B*18:01, -DRB1*01 and -C*04:01—The Significance of the New Molecular Background - Magdalena Stasiak (Journal of Clinical Medicine, 2020)
Subacute thyroiditis (SAT) is a thyroid inflammatory disease whose pathogenesis is still not completely defined. Previous viral infection is considered to be a triggering factor in genetically predisposed individuals. In about 70% of patients, susceptibility to SAT is associated with the HLA-B*35 allele. The correlation between SAT and other human leukocyte antigens (HLA) has not yet been unequivocally demonstrated and the genetic background is still unknown in about 30% of patients. The purpose of our study was to perform HLA genotyping using a next-generation sequencing method, to find out whether alleles other than HLA-B*35 are correlated with SAT morbidity. HLA-A, -B, -C, -DQB1, -DRB1 were genotyped using a next-generation sequencing method in 1083 subjects, including 60 SAT patients and 1023 healthy controls. Among 60 patients diagnosed with SAT, 81.7% of subjects were identified as having allele HLA-B*35, 23.3% had HLA-B*18:01, 28.3% had HLA-DRB1*01 and 75.5% had HLA-C*04:01. These alleles occurred in the control group at frequencies of 10.2%, 7.2%, 12.9% and 12.5%, respectively. The differences were statistically significant, with p < 0.05. In addition to its previously described relationship with HLA-B*35, genetic susceptibility to SAT was associated with the presence of HLA-B*18:01, DRB1*01 and C*04:01. The alleles HLA-B*18:01 and DRB1*01 were independent SAT risk factors. The assessment of these four alleles allows the confirmation of genetic predisposition in almost all patients with SAT.